Reconstruction of Thanthu Durbar, Bhaktapur: A Case Study (Journal of Science and Engineering, 2026)
Thanthu Durbar in Bhaktapur Durbar Square Complex is believed to have been a part of the historic Thanthu Durbar, which means "Upper Palace" in Nepal Bhasha, indicating its position on higher ground relative to the main palace complex. Historically, it served as the Safaai Addha (Cleaning Department) in 2004 B.S. and was later repurposed as the municipal office of Bhaktapur Municipality. Bhaktapur Municipality has undertaken the reconstruction of historic Rana style building dating back to the Malla period. This paper presents a research project focused on employing archaeological and architectural studies through indigenous construction techniques. The methodology involved comprehensive site surveys, documentation, archaeological excavation, and consultations with conservation architects, historians, and archaeologists. This paper highlights the ongoing reconstruction process of building in architectural style of the Malla period in accordance with the research and excavation study results and its adherence to traditional construction techniques. The reconstruction of the building serves as a significant step towards safeguarding Nepal's architectural heritage and promoting sustainable approaches to heritage preservation. The reconstruction project aims to reconstruct the durbar to its Malla period design regarding archaeological research and structurally safeguarding the building. The findings from this research project contribute to the broader understanding of heritage reconstruction practices in Nepal and provide insights into the preservation of cultural heritage in seismic-prone regions. The reconstruction of the durbar of heritage site serves as a significant step towards safeguarding Nepal's architectural heritage and promoting sustainable approaches to heritage preservation.